Association between workplace violence and occupational stress among emergency department nurses: a cross-sectional study - Long, Lixi; Xie, Nan; Chen, Xiaoli; Zhang, Hao; Zhong, Luying; Diao, Dongmei; Zhu, Ling; Zhou, Yue (Frontiers in Public Health, 2025)
BackgroundEmergency department (ED) nurses suffer from workplace violence (WPV) and occupational stress (OS) due to the working environment. However, a relatively small number of studies on the relationship between WPV and OS among ED nurses have been conducted and its impact on nurse health or nursing quality.MethodsA cross-sectional study was conducted in 30 hospitals in China from December 26, 2023, to January 18, 2024 through questionnaire survey and stratified cluster sampling.ResultsA total of 1,540 ED nurses were surveyed, 1,309 of whom had experienced WPV. OS score of these ED nurses was (55.55 ± 16.78). Correlation between WPV and OS was significant (rs = 0.577, P < 0.01), and multivariate regression analysis revealed that an education level of bachelor's degree or higher; weekly working hours of 41–48, 49–58, and ≥59 h; physical violence experience; and psychological WPV were key influencing factors of OS among ED nurses.ConclusionA high proportion of ED nurses had experienced WPV, they had moderate to severe levels of OS, and WPV was a direct predictor of OS among them. This may be reduced by strengthening the management of violence in their workplace.